FORMATION AND PECULIARITIES OF COMMUNICATION THROUGH A COMMUNICATIVE APPROACH (International journal of artificial intelligence, 2024)
the most well-known current approach to Language Teaching is the communicative approach. And communication is an important condition for human life and activity. It is with the help of communication that humans have the opportunity to work together to meet their individual needs.